Memories are made of this : exploring argumentation in popular texts : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Palmerston North, New Zealand - Howard, Christina Mary (Massey University, 2004)
The role of discourse in the construction of institutional and academic knowledge is now recognised within a wide variety of theoretical perspectives, including social constructionism, the sociology of scientific knowledge, the rhetoric of inquiry and discursive psychology. The purpose of this study was to examine the ways in which such discursive knowledge construction practices occur in relation to psychological phenomena. The site of this investigation was the highly contentious debate surrounding the reality of repressed/recovered memories of childhood sexual abuse. Ten 'popular' psychology texts (five supporting the concept of recovered memories and five questioning it) were discursively and rhetorically analysed in order to gain an understanding of how the authors of these texts deployed arguments to support their own positions and undermine those of their opponents. Five broad rhetorical resources were identified as being prominent in the texts, each of which was examined in detail to determine more specifically the source of their persuasive power. The five resources included authorial credibility, definitions, science, history and personal experience. Despite the meta-rhetoric surrounding the debate, which suggests that it is essentially an argument between researchers (drawing on scientific evidence) and clinicians (drawing on clinical experience), what was apparent was that all of these resources were utilised to varying degrees to support both pro- and anti- recovered memory positions. This analysis suggested that a reasonably structured set of discursive resources were available for making arguments about the nature of psychological phenomena. Furthermore, when given the opportunity, rhetors utilised as many of these resources as possible in order to produce a convincing argument, even when this resulted in inconsistencies within their texts. It was concluded that in the memory debate, the demands of the rhetorical imperative (to persuade the audience) often appear to be paramount, and should not be discounted by those seeking to understand this difficult and often distressing topic.
Keywords: Repressed memory; False memory; Psychology texts; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380102 Learning, memory, cognition and language